Finite element modelling of magma convection and attendant groundwater flow - Harrison, Keith (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1998)
This thesis describes preliminary two- and three-dimensional modelling of mass and heat transport of hot, molten magma in crustal intrusions and of the associated thermally induced flow of groundwater contained in the surrounding country rock. The aim of such modelling is to create a tool with which to predict the location of mineral deposits formed by the transport and subsequent precipitation of minerals dissolved in the convecting groundwater. The momentum equations (Navier-Stokes equations), continuity equation and energy equation are used in conjunction with specially constructed density and viscosity relationships to govern the mass and heat transport processes of magma and groundwater. Finite element methods are used to solve the equations numerically for some simple model geometries. These methods are implemented by a commercial computer software code which is manipulated with a control program constructed by the author for the purpose. The models are of simple two- or three-dimensional geometries which all have an enclosed magma chamber surrounded completely by a shell of country rock through which groundwater is free to move. Modelling begins immediately after the intrusive event when the magma (in most cases rhyolitic) is at its greatest temperature. Heat is allowed to flow from the magma into the country rock causing thermal convection of the groundwater contained therein. The effect of the country rock as a porous medium on the flow of groundwater is modelled by including a distributed resistance term in the momentum equation. The computer code that controls the modelling is such that adaptions made to the models to represent real physical intrusive systems are trivial. Results of the research at this stage allow approximate prediction of the location of mineral deposits. Enhanced predictions can be made by effecting improvements to the models such as a more detailed representation of chemical processes, adaption of the computer code to allow multiple injections of magma and the modelling of frozen magma as a porous medium which admits the flow of groundwater.
Keywords: Groundwater flow; Magmas